Cooperative control of virtual energy storage devices for energy regulation and rapid frequency support - Yang, Zheng; Wang, Yi; Wei, Jiahui; Cao, Yabo (Frontiers in Energy Research, 2025)
Various controllable resources contribute to energy regulation and rapid support in the form of virtual energy storage (VES), which can significantly simplify control parameters and facilitate the evaluation of a microgrid’s economic and secure operational reserves. This paper establishes a power density virtual energy storage (PDVES) model and an energy density virtual energy storage (EDVES) model. Wind turbines, photovoltaics (PVs), controllable loads, and electric vehicles (EVs) are equated to EDVES and PDVES, respectively. Furthermore, an economic calculation model for microgrids that incorporates VES is developed, and an energy regulation framework for microgrids is constructed with virtual current (VCU) and virtual capacitor (VCA) as scheduling parameters. With the frequency security of island microgrids as a constraint, a rapid support coordinated control strategy for PDVES and EDVES is proposed to ensure the economic and secure operation of microgrids across multiple time scales. Finally, a high-proportion renewable energy test system with VES is established. The test results demonstrate that under the proposed VES control, the energy regulation and dynamic stability control performance of microgrids can be significantly improved.